2016
DOI: 10.1371/journal.pone.0161023
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 Increases Proliferation and Cisplatin Sensitivity of Osteosarcoma-Derived Cells

Abstract: Osteosarcoma is the most common primary bone tumor and poor prognosis for osteosarcoma patients is mainly due to chemotherapy resistance. MicroRNAs are important to maintain pathophysiological mechanisms of cancer and influence cell sensitivity to chemotherapy. In this study, we tested the functions of microRNA-21 for malignant features as well as for drug resistance of osteosarcoma. We used Northern blot to measure microRNA-21 levels in osteosarcoma-derived cell lines. MicroRNA-21 activity was modulated by ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 47 publications
3
40
0
1
Order By: Relevance
“…PTEN, an anticancer factor, is inactivated by miR‐21 in the development of GC. [ 41 ] Similarly, our results also showed that the level of PTEN was reduced after transfection with miR‐21 mimic. For the first time, we showed the regulatory relationship between circHIAT1, miR‐21, and PTEN/PI3K/AKT and ERK.…”
Section: Discussionsupporting
confidence: 73%
“…PTEN, an anticancer factor, is inactivated by miR‐21 in the development of GC. [ 41 ] Similarly, our results also showed that the level of PTEN was reduced after transfection with miR‐21 mimic. For the first time, we showed the regulatory relationship between circHIAT1, miR‐21, and PTEN/PI3K/AKT and ERK.…”
Section: Discussionsupporting
confidence: 73%
“…Thus, in this study, we investigated the impact of miR-765 on the anti-angiogenic effect of cisplatin. Several studies have shown the impact of miR-21 on sensitivity of osteosarcoma-derived cells towards chemotherapies 18 . MicroRNAs are critical oncomiRs in tumorigenesis, and their expression has been shown to be up-regulated in breast carcinoma 19 .…”
Section: Discussionmentioning
confidence: 99%
“…miR-378 was shown to reverse resistance to cisPt in lung adenocarcinoma cells [134], whereas miR-27a was shown to be upregulated in a multidrug resistant ovarian cancer cell line, contributing to cisPt resistance [135]. miR-21 increases the cisPt sensitivity of osteosarcoma-derived cells [136]. For references to particular studies using cisPt, refer to Table 1.…”
Section: Compoundsmentioning
confidence: 99%